ACTIVITY OF GEMSINTETAZA MITOCHONDRIA BRAIN CORTEX DUE TO DISTURBANCES OF PORPHYRIN METABOLISM - Kryzhnaya, S.I. (World of Medicine and Biology, 2010)
There are shown the results of studies activity gemsintetazy in rats with experimental disturbances of porphyrin metabolism. It is established that activity of brain cortex mitochondria is reduced in experiments in vitro and in vivo and depends on the concentration of benzene.
Keywords: disorders of porphyrin metabolism; gemsintetaza; intoxication by benzene